Intravenous sedation and nursing management for a patient with dental anxiety (1例重度牙科焦虑症患者静脉镇静治疗的护理体会) - WANG Wei (王威); GAN Ling (甘泠); MA Yumei (马玉梅); WU Xuan (吴宣); ZHANG Xiaowei (张晓巍); YAN Tong (晏桐); LI Jiayao (李加尧) (中西医结合护理)
This paper summarized the intravenous sedation and nursing practice for a patient with dental anxiety. A comprehensive nursing assessment on dental fear and psychological status of the patient was conducted before intravenous sedation, and an individualized nursing plan was conducted. A highly skilled nursing team was built to ensure the success of dental surgery and emergency treatment. Standard nursing procedure was provided throughout the process of diagnosis, treatment and follow-up, in order to relieve the anxiety of the patient and ensure the success of oral treatment. (本文总结1例重度牙科焦虑症患者静脉镇静治疗的护理经验。通过全面细致的护理评估, 了解患者的牙科畏惧程度和心理状况, 开展静脉镇静治疗, 制定个性化护理计划; 组建技术精湛的护理团队, 确保操作熟练、急救能力过硬; 实施同质化护理, 采用标准化沟通话术, 贯穿模拟就诊、治疗及随访全程, 有效缓解患者紧张情绪, 保障患者顺利完成口腔治疗。)